ANALISIS FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Octaviani, Dian; Hastuti, Rini Tri (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to examine the effect of free cash flow, leverage, and liquidity on dividend policy with firm size as moderating. The research data that is processed is from the financial statements of 2018 – 2020 on Manufacturing Companies that are legally registered on the IDX. Data samples were taken by purposive sampling. Data processing and analysis using multiple linear regression with the help of SPSS 25 program. The results showed that free cash flow had a positive and significant effect on dividend policy, leverage had an insignificant negative effect on dividend policy, liquidity had an insignificant positive effect on dividend policy. Moderation results show that firm size is not a moderating variable of the effect of free cash flow, leverage, and liquidity on dividend policy.